Effect of therapeutic ultrasound of low intensity pulsed and continuous in fibroblastic cells in vitro - Oliveira, Priscila Daniele de; Pires-Oliveira, Deise Aparecida Almeida; Pacheco-Soares, Cristina; Szezerbaty, Stheace Kelly Fernandes; Spadaccini, Ana Flávia; Bertin, Larissa Dragonetti; Silva, Jéssica Lucio da; Santos, Adriele Flausino dos; Oliveira, Rodrigo Franco de (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: The ultrasound is widely used clinical practice focused on tissue repair, because it is a secure resource, minimally-invasive and low investment. However, despite the effects of ultrasound have been well described, the ideal relationship between dose and effect, still needs to be better elucidated and bounded. Objective: In this way, the objective of this study was to evaluate the influence of irradiation pulsed ultrasound and continuous in the viability of fibroblastic cells L929 in vitro. Method: The cells were distributed in TPP plates 12 wells in the concentration of 5x105 cells/µL and subdivided into the following groups: G1: control (not received radiation), G2: irradiated to 0.5 W/cm2 - 30% and G3: irradiated to 0.5 W/cm2 - 100%. Then received ultrasonic irradiation with intervals of 24, 48 and 72 hours, and after 24 hours of each irradiation was performed MTT cytotoxicity cell. Results: Among the three groups analyzed, only the G2 group showed a significant difference between the time 48 and 72 hours (p=0.05). In other times, despite variation in the percentage of viable cells, were not significant. When compared to peers at post-test, it was possible to observe a difference of 29% of viable cells between the groups G1 and G2 (p=0.05). However, the biggest difference was observed between the groups G2 and G3 (p=0.05). Conclusion: In this way, it can be concluded that irradiation pulsed ultrasound showed higher proliferation of fibroblasts L929 in time 48 hours, whereas in group irradiated in continuous mode, there was no statistically significant difference between the times.